Radiation oncology: physics advances that minimize morbidity. (December 2014) - Allison, Ron R; Patel, Rajen M; McLawhorn, Robert A
ABSTRACT : Radiation therapy has become an ever more successful treatment for many cancer patients. This is due in large part from advances in physics including the expanded use of imaging protocols combined with ever more precise therapy devices such as linear and particle beam accelerators, all contributing to treatments with far fewer side effects. This paper will review current state-of-the-art physics maneuvers that minimize morbidity, such as intensity-modulated radiation therapy, volummetric arc therapy, image-guided radiation, radiosurgery and particle beam treatment. We will also highlight future physics enhancements on the horizon such as MRI during treatment and intensity-modulated hadron therapy, all with the continued goal of improved clinical outcomes.